Serotonin - Qu, Ying (IntechOpen, 2019)
My scientific journey brought me from Lanzhou in China, Leuven in Belgium, Bethesda in the USA, all the way to San Diego. Sometimes I pick up an assortment of scattered seashells while walking along the beautiful Torrey Pines Beach in San Diego. Likewise, this book contains an assortment of discussions of different aspects of serotonin to enrich our knowledge and understanding of this neurochemical. The book contains four different chapters: 1. Introductory chapter: From Measuring Serotonin Neurotransmission to Evaluating Serotonin Post-Receptor Signaling Transduction; 2. Serotonin Reuptake Inhibitors and Their Role in Chronic Pain Management; 3. Serotonin and Emotional Decision-Making; and 4. Clinical Aspects Related to Plasma Serotonin in the Horse.